The significance of respiration timing in the energetics estimates of free-ranging killer whales (Orcinus orca) - Roos, Marjoleine Merel Hansje; Wu, Gi-Mick; Miller, Patrick (Journal of Experimental Biology, 2017)
Respiration rate has been used as an indicator of metabolic rates and associated cost-of-transport (COT) of free-ranging cetaceans, discounting potential respiration-by-respiration variation in O2 uptake. To investigate the influence of respiration timing on O2 uptake we developed a dynamic model of O2 exchange and storage. Individual respiration events were revealed from kinematic data from ten adult Norwegian herring-feeding killer whales (Orcinus orca) recorded with high-resolution tags (DTAGs). We compared fixed-O2-uptake-per-respiration models to O2 uptake per respiration estimated through a simple 'broken-stick' O2-uptake function, in which O2 uptake was assumed to be the maximum-possible O2 uptake when stores are depleted or maximum total body O2 store minus existing O2 store when stores are close to saturated. Conversely to assuming fixed O2 uptake per respiration, uptake from the broken-stick model yielded a high correlation (r2 > 0.9) between O2 uptake and activity level. Moreover, we found that respiration intervals became less variable and increased at higher swimming speeds, possibly to increase O2 uptake efficiency per breath. As found in previous studies, COT decreased monotonically versus speed using the fixed-O2-uptake-per-respiration models. However, the broken-stick uptake model yielded a curvilinear COT-curve with a clear minimum at typical swimming speeds of 1.7-2.4 m s-1. Our results showed that respiration-by-respiration variation in O2 uptake is significant. And though O2 consumption measurements of COT for free-ranging cetaceans remain impractical, accounting for the influence of respiration timing on O2 uptake will lead to more consistent predictions of field metabolic rates than using respiration rate alone. Peer reviewed